Антропоморфный персонаж на печатях Ирана и Месопотамии - Антонова, E.B.
Antonova, E.V., Towards an Interpretation of the Anthropomorphic Images that Appear on Iranian and Mesopotamian Seals; Engl. Summary; 4. Jh.v.Chr.